Does financial inclusiveness matter for the formal financial inflows? Evidence from Pakistan - Mariam Naz; Syed Faizan Iftikhar; Ambreen Fatima (Quantitative Finance and Economics, 2020)
The remittance inflows are the major source of financial transfers received by households to maintain their livelihood. However, the formal inflows can play an immense role in improving the indigenous economy by affecting household welfare, these flows further strengthen the economy at micro and macro levels. Previously, various studies found a determinant relationship between supply-side factors and financial inclusion. Whereas, this paper emphasizes a sweltering issue of formal financial inflows in Pakistan especially focusing on the demand side factors on the household level. The analysis uses Heckman Selection Technique to assess the demand for formal financial inclusion which can only be realized for the households receiving remittances, where the determinants for both depend upon the distinctive demographic, individuals and household characteristics. The study appraises household survey data from the Household Integrated Economic Survey (HIES) for the period 2013–2014. The results demonstrate the strong effects of households’ demand-side factors on financial inclusion. The demographic features such as education and the highest earner’s age are found to have a positive and significant impact on financial inclusion. Whereas, the household characteristics such as household living conditions, asset accumulation, household savings, and borrowings also strongly affect the formal financial inclusive decision. It is therefore suggested to employ a comprehensive policy regarding the enhancement of households’ awareness by the spread of formal and financial literacy.